MiR-494-3p promotes PI3K/AKT pathway hyperactivation and human hepatocellular carcinoma progression by targeting PTEN - Lin, Hui (Sci Rep, 2018)
Recent studies have shown that miR-494-3p is oncogene and has a central role in many solid tumors; however, the role of miR-494-3p in the progression and prognosis of hepatocellular carcinoma (HCC) remains unknown. In this study, it was found that miR-494-3p was up-regulated in HCC tissues. The high level of miR-494-3p in HCC tumors was correlated with aggressive clinicopathological characteristics and predicted poor prognosis in HCC patients. Functional study demonstrated that miR-494-3p significantly promoted HCC cell metastasis in vitro and vivo. Since phosphoinositide 3-kinase/protein kinase-B (PI3K/AKT) signaling is a basic oncogenic driver in HCC, a potential role of miR-494-3p was explored as well as its target genes in PI3K/AKT activation. Of all the predicted target genes of miR-494-3p, the tumor-suppressor phosphatase and tensin homolog (PTEN) were identified. In conclusion, the data we collected could define an original mechanism of PI3K/AKT hyperactivation and sketch the regulatory role of miR-494-3p in suppressing the expression of PTEN. Therefore, targeting miR-494-3p could provide an effective therapeutic method for the treatment of the disease.